Development of HPLC with fluorescent detection using NBD‐F for the quantification of colistin sulfate in rat plasma and its pharmacokinetic applications. (7th January 2018) - Ouchi, Sui; Matsumoto, Kazuaki; Okubo, Maki; Yokoyama, Yuta; Kizu, Junko
Abstract: Colistin sulfate, composed of a mixture of colistin A sulfate (CLA) and colistin B sulfate (CLB), is available for treating life‐threatening infections caused by multidrug‐resistant Gram‐negative bacteria. In this study, the CLA and CLB were quantified separately. Colistin sulfate was extracted from rat plasma with a solid‐phase extraction C18 cartridge and reacted with 4‐fluoro‐7‐nitro‐2, 1, 3‐benzoxadiazole (NBD‐F), and the fluorescent derivatives were subjected to reversed‐phase high‐performance liquid chromatography analysis and used to investigate the pharmacokinetics of CLA and CLB in rat plasma. The recovery rates of CLA and CLB were 41.2 ± 4.4 and 45.5 ± 3.1%, respectively. The recovery rate calculated from the total area of CLA and CLB was 43.9 ± 3.6%. When 2 mm NBD‐F and 10 mm boric acid buffer (pH 9.5) were added to colistin sulfate, the highest recovery rate was obtained. The best heating time was 5 min at 60°C. The lower limits of quantification for CLA, CLB and the total area of CLA and CLB were 0.05, 0.05 and 0.1 μg/mL; the coefficients of variations were 13.5, 14.5 and 14.1%, respectively. This method was found to have acceptable linearity, precision and accuracy, and has been successfully applied to a pharmacokinetic study in rat plasma.